2022
DOI: 10.1017/cjn.2022.267
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-2019 and Stroke: Pathophysiology and Management

Abstract: Severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease-2019, has been associated with an increased risk for ischemic and hemorrhagic stroke. As data emerge about the underlying mechanisms, it is important to synthesize current knowledge to improve effective treatment options. In this review, we highlight the known pathophysiology, discuss the relationship between ischemic and hemorrhagic stroke, and address emerging implications for patient management. The information here i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…The COVID-19 pandemic has placed unprecedented strain on stroke services globally, disrupting healthcare delivery and raising concerns about its impact on stroke outcomes ( 85 ). Despite these challenges, our meta-analysis did not identify any explicit instances linking the pandemic with influential impacts on stroke management or patient outcomes across included studies.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has placed unprecedented strain on stroke services globally, disrupting healthcare delivery and raising concerns about its impact on stroke outcomes ( 85 ). Despite these challenges, our meta-analysis did not identify any explicit instances linking the pandemic with influential impacts on stroke management or patient outcomes across included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one of the symptoms of the patient in the current study was hemiparesis accompanying acute-onset psychiatric symptoms, which may implicate a neuroinvasive effect of the virus. It has been reported that subarachnoid hemorrhage, ischemic and hemorrhagic stroke could be induced by SARS-CoV-2 with several mechanisms including hypercoagulability, dysregulated renin-angiotensin system, endothelial dysfunction, and neuroinvasion ( Panther and Lucke-Wold, 2022 , Small et al, 2022 ). Although hemiparesis has been previously associated with the concurrent ischemic stroke in COVID-19, as far as we know, this is the first patient developed hemiparesis without an ischemic cerebrovascular incident, in the literature ( Hamidi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has also been associated with an increased risk for ischemic and hemorrhagic strokes[ 21 ], conditions often treated with a vascular intervention procedure very similar to TACE that is achieved by embolizing the vessels connected to the aneurysm. Unlike liver vessels, intracranial vessels are not affected by respiratory motion and remain static with the use of X-ray images for guidance.…”
Section: Discussionmentioning
confidence: 99%